2020
DOI: 10.2147/ott.s249827
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA 691 Regulated PTEN/PI3K/AKT Signaling Pathway in Osteosarcoma Through miRNA-9-5p</p>

Abstract: Background: Large amounts of researches indicate that non-coding RNAs play a crucial role in many malignancies. However, the potential mechanisms of non-coding RNAs involved in osteosarcoma tumorigenesis remain elusive. Materials and Methods: The expression of long non-protein coding RNA 691 (lncRNA 691) in cell lines and paired osteosarcoma tissues was compared by qRT-PCR assay. Then, we explored the tumor suppressor function of lncRNA 691 with MTS and colony formation assay. Flow cytometry results showed lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Since the aberrant DNA methylation was proven to be associated with the OS tumorigenesis, it may serve as a predictive biomarker for OS prognosis ( 18 , 30 ). The DNA methylation genes, including FGD1, METTL3, ALKBH5, and PTEN, are associated with OS tumorigenesis reported in many previous studies ( 23 , 31 - 33 ) list of them keeps growing. It has been reported that methylation of frizzled-related proteins (SFRPs) may promote the Wnt signaling pathway, thereby enhancing OS cell invasion ( 34 ).…”
Section: Discussionmentioning
confidence: 94%
“…Since the aberrant DNA methylation was proven to be associated with the OS tumorigenesis, it may serve as a predictive biomarker for OS prognosis ( 18 , 30 ). The DNA methylation genes, including FGD1, METTL3, ALKBH5, and PTEN, are associated with OS tumorigenesis reported in many previous studies ( 23 , 31 - 33 ) list of them keeps growing. It has been reported that methylation of frizzled-related proteins (SFRPs) may promote the Wnt signaling pathway, thereby enhancing OS cell invasion ( 34 ).…”
Section: Discussionmentioning
confidence: 94%
“…e study showed that CDKN1A upregulation induced by miR-93-5p CDKN1A could block the TGF-β and thus increase the therapeutic effects of chemotherapy on small cell lung cancer cells [29]. miRNA-9-5p has been found to upregulate and activate PI3K/AKT pathways in osteosarcoma [30].…”
Section: Discussionmentioning
confidence: 98%
“…The study showed that CDKN1A upregulation induced by miR-93-5p CDKN1A could block the TGF- β and thus increase the therapeutic effects of chemotherapy on small cell lung cancer cells [ 29 ]. miRNA-9-5p has been found to upregulate and activate PI3K/AKT pathways in osteosarcoma [ 30 ]. Besides, miR-485-3p has been also proved to be involved in the cancer development via regulating TGF- β pathways, and RUNX2 has been widely confirmed as the downstream factors of TGF- β .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant regulation of lncRNAs is associated with tumor development and carcinogenesis, and lncRNAs may be applied as diagnostic, prognostic or therapeutic biomarkers for several types of cancer, including gastric cancer ( 29 ), osteosarcoma ( 30 ) and ovarian cancer ( 31 33 ). For example, Zhao et al ( 34 ) reported that the lncRNA LINC00092 induces glycolysis in fibroblasts associated with cancer, and influences the progression of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%